Advance Care Planning in Patients with Primary Malignant Brain Tumors: A Systematic Review - Song, Krystal; Amatya, Bhasker; Voutier, Catherine; Khan, Fary (Frontiers in Oncology, 2016)
Advance care planning (ACP) is a process of reflection and communication of a person’s future health care preferences, and has been shown to improve end-of-life care for patients. The aim of this systematic review is to present an evidence-based overview of ACP in patients with primary malignant brain tumours (pmBT). A comprehensive literature search was conducted using medical and health science electronic databases (PubMed, Cochrane, Embase, MEDLINE, ProQuest, Social Care Online, Scopus and Web of Science) up to July 2016. Manual search of bibliographies of articles and grey literature search were also conducted. Two independent reviewers selected studies, extracted data and assessed the methodologic quality of the studies using the Critical Appraisal Skills Program’s appraisal tools. All studies were included irrespective of the study design. A meta-analysis was not possible due to heterogeneity amongst included studies; therefore, a narrative analysis was performed for best evidence synthesis. Overall, 19 studies were included (1 RCT, 17 cohort studies, 1 qualitative study) with 4686 participants. All studies scored “low to moderate” on the methodological quality assessment, implying high risk of bias. A single RCT evaluating a video decision support tool in facilitating ACP in pmBT patients showed a beneficial effect in promoting comfort care and gaining confidence in decision–making. However, the effect of the intervention on quality of life and care at the end-of-life were unclear. There was a low rate of use of ACP discussions at the end-of-life. Advance Directive completion rates and place of death varied between different studies. Positive effects of ACP included lower hospital readmission rates, and intensive care unit utilization. None of the studies assessed mortality outcomes associated with ACP. In conclusion, this review found some beneficial effects of ACP in pmBT. The literature still remains limited in this area, with lack of intervention studies, making it difficult to identify superiority of ACP interventions in pmBT. More robust studies, with appropriate study design, outcome measures and defined interventions are required to inform policy and practice.